2000
DOI: 10.1002/(sici)1521-3749(200003)626:3<613::aid-zaac613>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Crystal Structure of a Novel Dinuclear Copper(II) Complex, [Cu2(phen)2(H2O)2(OH)2](HCO3)2 · 6 H2O with phen = 1,10-phenanthroline

Abstract: Dark blue plate‐like crystals of [Cu2(phen)2 · (H2O)2(OH)2](HCO3)2 · 6 H2O were obtained from a CH3OH–H2O solution containing CuCl2, 1,10‐phenanthroline (phen), sebacic acid and Na2CO3. The crystal structure (triclinic, P 1 (no. 2), a = 8.118(1), b = 9.624(1), c = 10.536(1) Å, α = 81.35(1)°, β = 88.51(1)°, γ = 75.77(1)°, Z = 1, R = 0.0332, wR2 = 0.0981 for 4163 observed reflections (F $^2_o$ ≥ 2σ(F $^2_o$) out of 4595 unique reflections) consists of divalent [Cu2(phen)2(H2O)2(OH)2]2+ complex cations, anionic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Because of inversion symmetry, the two apical water molecules are in a trans conformation. This dinuclear cation is similar to others reported previously (Zheng et al, 2000;Lu et al, , 2004. The CuÁ Á ÁCu distance of 2.911 (3) Å in (I) is longer than that found in [Cu 2 (C 12…”
Section: Commentsupporting
confidence: 90%
See 1 more Smart Citation
“…Because of inversion symmetry, the two apical water molecules are in a trans conformation. This dinuclear cation is similar to others reported previously (Zheng et al, 2000;Lu et al, , 2004. The CuÁ Á ÁCu distance of 2.911 (3) Å in (I) is longer than that found in [Cu 2 (C 12…”
Section: Commentsupporting
confidence: 90%
“…[2.902 (1) Å ; Zheng et al, 2000;Lu et al, 2004] and shorter than that found [2.933 (1) Å ] by Lu et al (2003).…”
Section: Commentmentioning
confidence: 70%